A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M., Kaim, Andrzej (2019): A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard. Acta Palaeontologica Polonica 64 (1): 101-141, DOI:10.4202/app.00554.2018, URL: http://dx.doi.org/10.4202/app.00554.2018